Perforated panel absorbers with micro-perforated partitions. (June 2019) - Carbajo, J.; Ramis, J.; Godinho, L.; Amado-Mendes, P.
Abstract: Some of the most extended approaches to widen the sound absorption bandwidth of perforated panel absorbers are the use of different cavity depths or multi-layer arrangements. Unfortunately, these solutions are rarely adopted in practice because of the technical installation difficulties or the large space requirements. This work explores an alternative compact solution consisting of a multi-size perforated panel absorber with micro-perforated partitioned cavities. While multi-size perforated panel absorbers with rigidly partitioned cavities show a wider sound absorption effective bandwidth when compared to those using single sized holes (i. e. multiple resonances instead of single resonance), the use of micro-perforated partitions was found to further broaden it and hence improve their sound absorption performance. A simplified approximate model for the prediction of the acoustic properties of such devices was derived using the Equivalent Circuit Method (ECM) and the Maa model for MPPs (Micro-Perforated Panels). Results in terms of the sound absorption coefficient under normal incidence showed a good agreement when compared to finite element simulations both for the cases with rigid and micro-perforated partitions. In addition, a parametric study was found very helpful to understand the influence of the geometrical features of the micro-perforated partitions on the acoustic behavior of the resonator, thus being useful for its design and analysis.